2020
DOI: 10.18805/ijare.a-585
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of True Shallot Seed (TSS) Varieties and Population on Growth and Bulb Yield

Abstract: Background: The purpose of this research was to evaluate the growth and bulb yield of shallot (Allium cepa L.) varieties grown by TSS with different population.Methods: This study was carried out in the low dry land at Laleten Village, Malaka District, NTT Province, Indonesia, from March to August 2018. We investigated different plant populations per planting hole using a split-plot design with two factors and four replications. The main plot was the varieties (Trisula and Bima Brebes) and the subplots were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…This is presumably because the Lokananta variety is more adaptive to environmental factors than Sanren F1 varieties so the growth rate is higher. This is supported by Devy et al 20 which has stated that the character of plants can be influenced by genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 74%
“…This is presumably because the Lokananta variety is more adaptive to environmental factors than Sanren F1 varieties so the growth rate is higher. This is supported by Devy et al 20 which has stated that the character of plants can be influenced by genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 74%
“…In another study, it was shown that the carbohydrate content of several shallot varieties tended to increase under shade stress conditions (data not shown). This shows that under stress conditions plants are able to form carbohydrates to compensate for respiration (Devy et al, 2021). 15.63 *) Numbers followed by the same lowercase letters in the same row are not significantly different, and numbers followed by the same capital letters in the same column are not significantly different, on Duncan's 5% test Shallot varieties and shade stress conditions did not significantly interact on the number of tubers.…”
mentioning
confidence: 89%
“…Differences in altitude result in differences in edaphic and climatic factors of the growing environment, which will result in the growth, production and physiological characters of shallot plants. Therefore, an analysis of the best cultivation methods in the highlands and in the lowlands is very important to do because the conditions of the highlands and lowlands are very specific in terms of IOP Publishing doi:10.1088/1755-1315/1241/1/012034 2 agro-climatic and edaphic factors [5][6].…”
Section: Introductionmentioning
confidence: 99%